2018
DOI: 10.1111/sji.12733
|View full text |Cite
|
Sign up to set email alerts
|

T11TS immunotherapy augments microglial and lymphocyte protective immune responses against Cryptococcus neoformans in the brain

Abstract: Cryptococcus neoformans, the encapsulated yeast acquired through inhalation, remains localized in lungs, but harbours the CNS in immunocompromised individuals. Several treatment regimes have failed combating this disease totally, but long‐term usage of drugs leads to organ damage. As T11‐target structure (T11TS) has documented profound immune potentiation, we aimed to investigate the role of microglia, pivotal immune cells of brain in ameliorating cryptococcosis, with T11TS immunotherapy. Murine model with C n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Since different lymphocyte phenotypes are also correlated with different lymphocyte function, we first established an immune scoring model based on combination of the number, function and phenotype of lymphocytes to comprehensively assess host immunity. The imbalance of immunity leads to many immune-related diseases, such as autoimmune disease (hyperimmune status) [30] and opportunistic infection (hypoimmune status) [31][32][33][34][35][36]. The validation data from patients with different immune status showed that the model had high sensitivities in the determination of both hyperimmune and hypoimmune status.…”
Section: Discussionmentioning
confidence: 99%
“…Since different lymphocyte phenotypes are also correlated with different lymphocyte function, we first established an immune scoring model based on combination of the number, function and phenotype of lymphocytes to comprehensively assess host immunity. The imbalance of immunity leads to many immune-related diseases, such as autoimmune disease (hyperimmune status) [30] and opportunistic infection (hypoimmune status) [31][32][33][34][35][36]. The validation data from patients with different immune status showed that the model had high sensitivities in the determination of both hyperimmune and hypoimmune status.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study showed that T11TS modulates the immunological synapse of T cells (data communicated). We have also shown that T11TS mediates the elimination of fungal burden in the rats' brains (Hazra et al 2019). 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 In our present study, we have attempted to dissect the role of major intracellular partners involved in the CaN-NFAT signalling pathway during C. neoformans infection and following T11TS immunotherapy.…”
Section: Discussionmentioning
confidence: 61%
“…One millilitre of T11TS (0Á4 mg kg À1 body weight) was administered to 7 days post-infected rats i.p., followed by a second, and a third booster dose, making a dosing schedule of 1, 2 and 3 ml to the CT1, CT2 and CT3 animals, respectively. For each dose, T11TS were injected at an interval of 6 days (Hazra et al 2019).…”
Section: Preparation Of T11ts and Its Administration In Animalsmentioning
confidence: 99%
See 2 more Smart Citations